Determinants of Loyalty in Business Banking - Fragata, A. (2017)
The aim of this study is to investigate and compare the main determinants of Banking Loyalty for Business Banking customers in an offline and online environment. The results showed that the major driver of Banking Loyalty in an offline environment is Perceived Service Quality. Satisfaction and Image overlap the last construct and business customers do not perceive Switching Costs. In an online context E-Banking Service Quality affects E-Banking Loyalty, E-Satisfaction and Image overlap the last construct, E-Banking Service Quality has a strong impact on E-Trust and Perceived Switching Costs has a strong impact on E-Banking Loyalty.